Importance of High C-Reactive Protein (CRP) And Total Leukocyte Count (TLC) In Odontogenic Space Infections - Sadia Rashid, Muhammad Adnan Iqbal, Muhammad Adeel, Sana Zafar, Shahida Maqbool, Danish Javed, Muhammad Rizwan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: An acute inflammatory homo-pentameric plasma protein, C-reactive Protein, discovered in 1930, is found in small amounts in healthy persons and plays an important role in natural immune system, activation of compliment system and phagocytosis and antigen clearance. Aim: To determine high C - reactive protein (CRP) and Total Leukocyte Count (TLC) in patients suffering from odontogenic space infections. Methods: Present study was carried out in the department of Oral Surgery at Islam Dental College, Sialkot from Sept. 2020 to Oct 2021. A total of 151 male and female patients of 22-65 years age range with odontogenic space infection were included. Patients suffering from chronic disease like diabetes, chronic renal failure, and pregnant women were excluded. Sample of patient’s blood was sent to the hospital laboratory for measurement of serum C - reactive protein (CRP) and Total Leukocyte Count (TLC) levels. Results: Patient’s age range in our study was 22 to 65 years with mean age of 54.5±14.68 years. Out of 151 patients, 93 (61.58%) were male and females were 58 (38.42%) showing male to female ratio of 1.6:1. Mean CRP levels were 3.52±1.23 mg/L and Mean TLC levels were 13670 ± 1890 cells/mm3. In our study, frequency of raised CRP levels was found in 100% and TLC in 71.82% of patients with odontogenic space infections. Conclusion: This study concluded that frequency of raised C-Reactive Protein (CRP) levels are found in 100% patients, indicating CRP to be an effective biomarker in infected patients.